2008
DOI: 10.3164/jcbn.2008066
|View full text |Cite
|
Sign up to set email alerts
|

Lemon Polyphenols Suppress Diet-induced Obesity by Up-Regulation of mRNA Levels of the Enzymes Involved in β-Oxidation in Mouse White Adipose Tissue

Abstract: Summary The aim of this study was to investigate the effect of dietary lemon polyphenols on high-fat diet-induced obesity in mice, and on the regulation of the expression of the genes involved in lipid metabolism to elucidate the mechanisms. Mice were divided into three groups and fed either a low fat diet (LF) or a high fat diet (HF) or a high fat diet supplemented with 0.5% w/w lemon polyphenols (LP) extracted from lemon peel for 12 weeks. Body weight gain, fat pad accumulation, the development of hyperlipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 49 publications
1
48
0
2
Order By: Relevance
“…Previous research examining the effect of polyphenols supplementation showed significantly up-regulated the acyl-CoA oxidase (ACO) mRNA level in epididymal fat [40]. In our study, quercetin group showed increased ACOX expression in skeletal muscle.…”
Section: Discussionsupporting
confidence: 61%
“…Previous research examining the effect of polyphenols supplementation showed significantly up-regulated the acyl-CoA oxidase (ACO) mRNA level in epididymal fat [40]. In our study, quercetin group showed increased ACOX expression in skeletal muscle.…”
Section: Discussionsupporting
confidence: 61%
“…Among all polyphenol compounds, chlorogenic acid-or quercetin-containing apple products have been shown to have anti-obesity effects in HFD-induced obesity [30,31]. Fukuchi et al [46] indicated that citrus bioactive phenolics were reported to promote less body weight gain and white adipose tissue gain in mice after feeding of a HFD. Acetic acid is a major ingredient of vinegar, representing 6% of vinegar by volume, and it has also been shown to affect metabolic regulation and to have weight-reducing effects and alleviate hyperlipidemia [17,19,20,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Body weight gain, fat accumulation, and the development of hyperlipidemia, hyperglycemia, and insulin resistance were significantly suppressed by lemon polyphenols in mice fed a highfat diet (53). Lemon polyphenols suppressed diet-induced obesity by upregulation of mRNA levels of the enzymes involved in b-oxidation, such as peroxisome proliferator activated receptor (PPAR) a, acyl-CoA oxidase, FA synthase in liver, and white adipose tissue in mice (53). Naringenin supplementation (0.003%, 0.006%, and 0.012% of the diet for 6 wk) lowered adiposity and TG contents in parametrial adipose tissue in rats (54).…”
Section: Effect Of Naringin On Obesitymentioning
confidence: 98%
“…High body fat also increases the risk of several diseases such as diabetes, hyperlipidemia, and hypertension, which leads to arteriosclerotic disease and metabolic syndrome (52). Body weight gain, fat accumulation, and the development of hyperlipidemia, hyperglycemia, and insulin resistance were significantly suppressed by lemon polyphenols in mice fed a highfat diet (53). Lemon polyphenols suppressed diet-induced obesity by upregulation of mRNA levels of the enzymes involved in b-oxidation, such as peroxisome proliferator activated receptor (PPAR) a, acyl-CoA oxidase, FA synthase in liver, and white adipose tissue in mice (53).…”
Section: Effect Of Naringin On Obesitymentioning
confidence: 99%